PEMANFAATAN LIMBAH PRAKTIKUM MENJADI PRODUK KRIYA IKAT PINGGANG WANITA - Nur Halimah; Sri Litawati (Narada : Jurnal Desain dan Seni, 2022)
The Education Laboratory has the main function as a provider of practicum facilities. Leather Products Workshop is included in the Education laboratory which provides student lecture practicum services. The practical work produced by students are bags, wallets, card wallets and ID card holders. The activity of making works involves processing materials using the equipment that has been provided. These activities also produce practicum waste that is not used. Handling of practical waste needs to be considered properly so that it does not contribute much to environmental pollution. The practicum waste generated by Leather Products Workshop is pieces of leather left over for making student practicum works. That waste were used in this study. The goal of this study is produce women belt. Belts have good visualization ini presenting waste utilization works. That products then described using a design approach with a qualitative descriptive method. The materials used are leather waste, synthetic glue and nylon thread. The equipment used are a hook, silver ink, scissors, round “plong”, “pandokan”, wooden hammer and sewing machine. The results of this work are craft products in women's belt with a combination of aesthetically knitting techniques. This study concludes that practical waste can be processed into craft works that have aesthetic value.